Dynamic Transparency for 3D Visualization: Design and Evaluation - Elmqvist, Niklas; Assarsson, Ulf; Tsigas, Philippas (International Journal of Virtual Reality, 2009)
Recent developments in occlusion management for 3D environments often involve the use of dynamic transparency, or "virtual X-ray vision", to promote target discovery and access in complex 3D worlds. However, there are many different approaches to achieving this effect and their actual utility for the user has yet to be evaluated. Furthermore, the introduction of semitransparent surfaces adds additional visual complexity that may actually have a negative impact on task performance. In this paper, we report on an empirical user study investigating these human aspects of dynamic transparency. Our implementation of the technique is an image-space algorithm built using modern programmable shaders to achieve real-time performance and visually pleasing results. Results from the user study indicate that dynamic transparency provides superior performance for perceptual tasks in terms of both efficiency and correctness. Subjective ratings are also firmly in favor of the method.